THE ANALYSIS OF THE SPEECH “WHAT ISLAM REALLY SAYS ABOUT WOMEN” BY ALAA MURABIT BASED ON THE PERSPECTIVE OF LINGUISTICS BEHAVIORISM - Lula Wahyu Anindita; Ubaidillah (Celtic : A Journal of Culture, English Language Teaching, Literature and Linguistics, 2024)
This study aims to explain the analysis of the meaning of a speech context delivered by Alaa Murabit in the speech "What Islam Really says about Women" on the TED YouTube channel (July 21, 2015) in order to help the audience in interpreting the context of meaning so as not to cause misunderstandings. This study uses the theory of Linguistic Behaviorism pioneered by Bloomfield (2013). The method used in analyzing data is a qualitative descriptive method by selecting some data in a speech that contains a mismatch of context with stimulus. The result of this study, Alaa Murabit, used two main stimuli: family background and religion, so that it gave rise to a response in the form of a parable sentence that has many interpretations.